Influence of the human intestinal microbiome on obesity and metabolic dysfunction. Issue 4 (August 2015) - Tilg, Herbert; Adolph, Timon E.
<x xml:space="preserve">Abstract</x> Purpose of review Recent studies have suggested that there may be a strong link between the gut microbiota, energy extraction and body metabolism. Recent findings Evidence is accumulating that the intestinal microbiota, in addition to other major factors such as diet and host genetics, contributes to obesity, metabolic dysfunction and diabetes. Both preclinical experimental and human studies have shown that obesity and metabolic dysfunction are characterized by a profound dysbiosis. Several human metagenome-wide association studies have demonstrated highly significant correlations of certain members of intestinal microbiota with obesity and type 2 diabetes. In addition dietary factors that substantially affect microbial composition, microbiota disruption, and the consequence of early-life antibiotic use, may contribute to childhood obesity and metabolic dysfunction. Further evidence for an association between microbiota and metabolic dysfunction has been derived from studies in pregnancy demonstrating that major gut microbial shifts occur during pregnancy thereby affecting host metabolism. In particular, the high rate of obesity following caesarean section could be partially explained by functional alterations in the intestinal microbiota. Summary Obesity and associated metabolic dysfunction emerge from disturbed interactions between the intestinal microbiota, dietary changes and host immune functions. A better understanding of this relationship might lead to better therapies for human metabolic and inflammatory diseases in the future.